Social-Emotional Stimulation of Early Childhood Through Adaptive Mobile Learning Media Based on Tri Hita Karana - Putu Aditya Antara; I Made Tegeh; Wulandari, I Gusti Ayu Agung Manik (Jurnal Pendidikan dan Pengajaran, 2025)
Lack of support and resources hampers children's development, thus impacting their social growth. Based on this, this study aims to analyze the effectiveness of Adaptive Mobile Learning-Based Learning Media on Early Childhood Social-Emotional. This type of research is qualitative research. The research design used at the product effectiveness stage is one group pre-test and post-test design. The intended pre-test is the trial subject to see social-emotional abilities. The effectiveness of developing THK-based adaptive mobile learning learning media involves all 19 children in the Kindergarten B group. The method used in collecting data is the observation method. The instrument used to collect data in this study is an observation sheet. The technique used in analyzing data is inferential statistics (t-test). The study results show differences in children's social-emotional abilities before and after participating in learning activities with THK-based adaptive mobile learning media in Kindergarten B children. It is concluded that THK-based adaptive mobile learning learning media can stimulate the social-emotional abilities of Kindergarten B children.